2002
DOI: 10.1046/j.1432-1327.2002.02847.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel nuclear transglutaminase that is expressed during starfish embryogenesis

Abstract: We report the constitution and molecular characterization of a novel transglutaminase (EC 2.3.2.13) that starts to accumulate specifically in the nucleus in the starfish (Asterina pectinifera) embryo after progression through the early blastula stage. The cDNA for the nuclear transglutaminase was cloned and the cDNA-deduced sequence defines a single open reading frame encoding a protein with 737 amino acids and a predicted molecular mass of 83 kDa. A comparison of this transglutaminase with other members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Instead, horseshoe crabs use the TGase cross-linking reaction during the final stage of coagulation . TGases have been found in other invertebrates but their functions are different or unknown (Singer et al, 1992;Sugino et al, 2002). In horseshoe crabs, hemolymph is extremely sensitive to minute amounts of bacterial LPS, which induces conversion of coagulogen (a soluble protein) into insoluble coagulin.…”
Section: Article In Pressmentioning
confidence: 99%
“…Instead, horseshoe crabs use the TGase cross-linking reaction during the final stage of coagulation . TGases have been found in other invertebrates but their functions are different or unknown (Singer et al, 1992;Sugino et al, 2002). In horseshoe crabs, hemolymph is extremely sensitive to minute amounts of bacterial LPS, which induces conversion of coagulogen (a soluble protein) into insoluble coagulin.…”
Section: Article In Pressmentioning
confidence: 99%
“…The enzyme is also involved in maintaining a toughened skin epidermis and hair follicle epithelia [5], in forming the fertilization plug in female rodents [6], in signal transduction, and in apoptosis [2,7]. In invertebrates, TGs were found in various species including the crayfish [8], horseshoe crab [9][10][11], grasshopper [12], starfish [13], fruitfly [14], tiger shrimp [15][16][17], and malaria mosquito [18]. Among invertebrates, in fruitfly and mosquito genomes, only one locus encoding TG with a functional domain organisation has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we decided to check their transcript levels in both sexes of rockshell, because blood coagulation often represents the first line of defense in several invertebrate immunity systems. To date, TG has been characterized in different marine invertebrate species, such as horseshoe crab [39], starfish [40], tiger shrimp [41], Chinese shrimp [42], and white leg shrimp [43]. In the present study, we found the TG gene from the rockshell EST database, and analyzed their different expression patterns in several rockshell tissues of male and female.…”
Section: Genementioning
confidence: 95%